Defining Inclusion: What It Is, What It Is Not, and Why It Matters - Sheppard, Steven (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2025)
Inclusion in education is often championed in policy but remains misunderstood and inconsistently applied in practice. This paper examines how inclusion is defined, implemented, and experienced, particularly for students with disabilities in Canadian schools. Drawing on Critical Disability Studies (CDS), legal policy analysis, and lived experience, this critique examines how segregation and deficit-based language continue to reinforce ableist structures despite claims of equity. Through personal narrative and a case study involving a student excluded from an art class, this paper illustrates how systemic design—not individual impairment—often disables. Key frameworks, including Kearney’s concept of hospitality and Krischler’s work on educator beliefs, are used to reframe inclusion not as mere placement but as a political and ethical commitment to transformation. This paper advocates for a paradigm shift—from integration into existing systems to the co-creation of inclusive spaces where all students are valued and feel a sense of belonging.